Revision: review of non-elective hospitalisations of adults with CHD. (10th July 2017) - Soufi, Alexandra; Colman, Jack M.; Li, Qunyu; Oechslin, Erwin N.; Kovacs, Adrienne H.
Abstract: Introduction: The adult CHD population is increasing and ageing and remains at high risk for morbidity and mortality. In a retrospective single-centre study, we conducted a comprehensive review of non-elective hospitalisations of adults with CHD and explored factors associated with length of stay. Methods: We identified adults (⩾18 years) with CHD admitted during a 12-month period and managed by the adult CHD service. Data regarding demographics, cardiac history, hospital admission, resource utilisation, and length of stay were extracted. Results: There were 103 admissions of 91 patients (age 37±10 years; 52% female). Of 91 patients, 96% had moderate or complex defects. Of 103 admissions, 45% were through the emergency department. The most common reasons for admission were arrhythmia (37%) and heart failure (28%); 29% of admissions included a stay in the ICU. The mean number of consultations by other services was 2.0. Electrophysiology and anaesthesiology departments were most frequently consulted. After removing outliers, the mean length of stay was 7.9±7.4 days (median=5 days). The length of stay was longer for patients admitted for heart failure (12.2±10.3 days; p=0.001) and admitted directly to the ward (9.6±8.9 days; p=0.009). Conclusions: Among non-electively hospitalised adults with CHD in a tertiary-care centre, management often entails an interdisciplinary approach, and the length of stay is longest for patients admitted with heart failure. The healthcare system must ensure optimal resources to maintain high-quality care for this expanding patient population.